Holistic nursing care among operating room nurses: Strengthening the standard of practice in Saudi Arabia - Hamdan Mohammad Albaqawi (Belitung Raya Foundation, 2021)
Background: Holistic practices have been found beneficial for patients as well as nurses. They increase both the nurses and the patients’ health-promoting behaviors, spirituality, and interpersonal relationships.